2010
DOI: 10.1172/jci43391
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinesis failure occurs in Fanconi anemia pathway–deficient murine and human bone marrow hematopoietic cells

Abstract: Fanconi anemia (FA) is a genomic instability disorder characterized by bone marrow failure and cancer predisposition. FA is caused by mutations in any one of several genes that encode proteins cooperating in a repair pathway and is required for cellular resistance to DNA crosslinking agents. Recent studies suggest that the FA pathway may also play a role in mitosis, since FANCD2 and FANCI, the 2 key FA proteins, are localized to the extremities of ultrafine DNA bridges (UFBs), which link sister chromatids duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 55 publications
11
110
0
Order By: Relevance
“…27,28 Third, the presence of anaphase bridges during mitosis in FA-deficient pathway cells can lead to cytokinesis failure and aneuploidy. 26 Finally, recent work has demonstrated a functional interplay between ERCC1/XPF and FANCD2 on mitotic chromosomes, both proteins interacting together in order to protect common fragile sites and avoid anaphase bridges and subsequent chromosomal instability. 33 Of note, as interwined chromatids may lead to gross chromosome loss or rearrangement, we investigated whether ERCC1-deficient A549 cells displayed genomic instability by performing CGH and cytogenetic analysis of the ERCC1-WT cell line and the ERCC1-deficient clones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Third, the presence of anaphase bridges during mitosis in FA-deficient pathway cells can lead to cytokinesis failure and aneuploidy. 26 Finally, recent work has demonstrated a functional interplay between ERCC1/XPF and FANCD2 on mitotic chromosomes, both proteins interacting together in order to protect common fragile sites and avoid anaphase bridges and subsequent chromosomal instability. 33 Of note, as interwined chromatids may lead to gross chromosome loss or rearrangement, we investigated whether ERCC1-deficient A549 cells displayed genomic instability by performing CGH and cytogenetic analysis of the ERCC1-WT cell line and the ERCC1-deficient clones.…”
Section: Discussionmentioning
confidence: 99%
“…26 The repair of these lesions relies on the FA pathway and on homology-directed repair, 2 processes likely to be affected by ERCC1 disruption. 27,28 Indeed, ERCC1 participates to the FA-mediated repair of ICLs and was shown to interact with FANCG.…”
Section: The Presence Of Anaphase Bridges In Ercc1-deficient Cells Ismentioning
confidence: 99%
“…BLM participates in the resolution of these bridges during mitosis and persistent DNA bridges may lead to micronucleation. (Chan, Palmai-Pallag et al 2009) Vinciguerra et al (Vinciguerra, Godinho et al 2010) demonstrated abnormally high number of ultrafine DNA bridges in cellular models of FA, which was correlated with a higher rate of cytokinesis failure and formation of binucleated cells.…”
Section: Cytokinesismentioning
confidence: 98%
“…However, the exact role of RIF1 in processing UFBs remains unclear. Other factors, such as TOPBP1 [63,64] and FANCM [65] also localize to certain types of UFBs (TOPBP1 on C-UFBs and FANCM on FS-UFBs).
10.1080/15384101.2018.1515555-F0002Figure 2.HR-UFBs arise in resolvase-deficient cells. U2OS cells were treated with siRNA against MUS81 and GEN1 to inactivate the SMX and GEN1 Holliday junction resolvases.
…”
Section: Proteins That Recognize and Process Hr-ufbsmentioning
confidence: 99%